Tumor neoantigens as key drivers of significant anti - tumor immunity in triple - negative breast cancer mouse models - Yujeong Her; Jeong Yeon Kim; Hocheol Shin; Kwangmin Yu; Kyu-Jin Lee; Yi Rang Na; Sangyong Jon; Jung Kyoon Choi; Hyeong-Gon Moon (Neoplasia: An International Journal for Oncology Research)
Recent studies have highlighted the therapeutic potential of targeting tumor neoantigens in solid tumors; however, its efficacy in breast cancer remains unclear. Here, we evaluate the impact of tumor neoantigen-targeted strategies in a syngeneic mouse mammary carcinoma model. Mice previously exposed to 4T1 tumor cells (PETCs) or treated with tumor cell-derived lysates (TdLs) exhibited robust antitumor immunity, leading to reduced tumor growth and metastasis through tumor immune microenvironment remodeling. TdL administration in mice harboring orthotopic tumors significantly enhanced the efficacy of immune checkpoint blockade, suggesting its potential as an immunotherapeutic adjuvant. To further optimize neoantigen-based approaches, we developed a lipid nanoparticle (LNP)-based delivery system for neoantigen peptides, which effectively suppressed tumor progression and metastasis in vivo. Mechanistically, this strategy promoted antigen-specific T cell activation and reshaped the tumor immune landscape, enhancing immune-mediated tumor rejection. These findings underscore the therapeutic promise of personalized tumor neoantigen-targeted immunotherapy in breast cancer and support its further evaluation in clinical settings.